O modelo de Schrödinger não linear com um defeito integrável - Silva, Douglas Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The theory of integrable defects in 1+1 ﬁeld theory, was introduced by the school of York [16, 17, 22], employing B¨acklund transformation in order to describe the defect. In this dissertation we have studied the nonlinear Schrödinger model in the presence of an integrable defect. We study both, the discrete model [29] as the continuous model within the lagrangian [23] andr matrix [7] formalisms. Also we built the hamiltonian formalism for nonlinear Schrödinger model in the presence of an integrable defect. We discuss and relate the lagrangian, hamiltonian and r matrix formalisms

A teoria de defeitos integráveis em teoria de campos em 1+1 dimensões, foi introduzida pela escola de York [16, 17, 22], utilizando transformações de Bäcklund para descrever o defeito. Nesta dissertação estudamos o modelo de Schrödinger não linear na presença de um defeito integrável. Estudamos tanto o modelo discreto [29] como o modelo contínuo dentro dos formalismos lagrangiano [23] e da matrizr [7]. Construímos também o formalismo hamiltoniano para o modelo de Schrödinger não linear na presença de um defeito integrável. Discutimos e relacionamos os formalismos lagrangiano, hamiltoniano e da matriz r
Keywords: Física matemática; Schrodinger, Equação de; Matriz r; Mathematical physics